IMPLEMENTASI PROGRAM MENGHAFAL AL-QUR’AN BEBRBASIS DIGITAL DALAM MENYESUAIKAN GAYA BELAJAR SANTRI - Tri Cahya Irani; Muliatul Maghfiroh (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2025)
Education is a very important human need. With educational assistance, someone can again knowlwdge and skills. Education also has the ability to help individuals who are independent and responsible. Penelitian This study aims to examine the implementation of a digital-based Quranmemorizing program in adjusting the learning style of student at IBS PKMKK Larangan Pamekasan. A qualitative approach is used in this study which involves conducting in-depth interviews, observing participants and analyzing relevant documents. Data analysis using Miles Huberman's interactive data analysis includes data collection, data condensation, data presentation, conclusion drawn/verification. Data wetness uses source triangulation. This study found that the use of digital applications such as interactive text-based and audio based murotal recordigs ang technology-based evaluation methods Can increase students’ motivation and memorizing retention. This program also allows fore more flexible ang personalized learning so that students can adjust their memorizing methods and learning styles. The obstacles faced include students who are lazy in memorizing and limited access to technology for some students as well as challenges in maintaining focus and discipline when using digital devices. Overall the implementation of the digital-based Quran memorizing program has a positive impact on improving the quality of students’ memorizing.